The best way to transcatheter aortic valve implantation: From standard to new approaches. (1st January 2021) - Morello, Alberto; Corcione, Nicola; Ferraro, Paolo; Cimmino, Michele; Pepe, Martino; Cassese, Mauro; Frati, Giacomo; Biondi-Zoccai, Giuseppe; Giordano, Arturo
Abstract: Transcatheter aortic valve implantation (TAVI) is a safe and beneficial treatment for patients with severe symptomatic aortic stenosis at high and intermediate surgical risk. The safety of the procedure continues to improve thanks to more refined procedural approaches and devices but, also and above all, to the accrual of the procedural knowledge and expertise by the operators. The diversification of the approaches and the possibility to tailor the treatment on the individual needs and anatomical features of the patients allows a rapid learning curve in the management of even complications. Indeed, there are several approaches with which TAVI can be carried out: transfemoral arterial, subclavian, transcarotid, transaortic, transaxillary, transapical, and through right anterior thoracotomy. Although transfemoral venous TAVI is less common, it has already have been carried out using caval-aortic punctures. This field is rapidly evolving, and it will be of paramount importance for interventional cardiologists and cardiothoracic surgeons to keep up to date with further developments. This review intends to give an in-depth and update overview of both conventional and innovative TAVI approaches, with the scope to highlight the relevant advantages, major disadvantages, safety aspects and techniques. Highlights: Analysis of the main accesses over time Description of the access technique Analysis of data in the literature concerning mortality and complications for each access with the attached table Analysis of the advantages and disadvantages of each access with an explanatory table Histograms of complications for lit